The Impact of Covid-19 on MSMEs and the Tourism Sector in Indonesia - Ambarwati, Annisa Dewi; Sudiantini, Dian (Jurnal Akuntansi, Manajemen dan Ekonomi, 2023)
indonesia is being shocked by the outbreak of the corona virus outbreak that started in China. As a result of this virus, many people in Indonesia and several other countries have died. The increase in positive cases that occur from day to day has caused a lot of losses in various sectors in Indonesia, especially the trade and tourism sectors. Indonesia as a country dominated by micro, small and medium enterprises (MSMEs) and the tourism sector, needs special attention to this sector because the contribution of MSMEs and the tourism sector to the national economy is quite important. The purpose of this study is to identify and analyze the impact of Covid-19 on MSMEs and the tourism sector in Indonesia. In writing using library research, namely in the process of collecting data, there is no need to go directly to the field, but take sources from various references to support this research. The method used is a qualitative method. The results of this journal research are to see and analyze the impact of Covid-19 on MSMEs and the tourism sector in Indonesia and what are the solutions or steps in helping to recover in the Covid-19 pandemic situation.